2004
DOI: 10.1890/02-5364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roadside Bias on the Accuracy of Predictive Maps Produced by Bioclimatic Models

Abstract: Sampling bias is a common phenomenon in records of plant and animal distribution. Yet, models based on such records usually ignore the potential implications of bias in data collection on the accuracy of model predictions. This study was designed to investigate the effect of roadside bias, one of the most common sources of bias in biodiversity databases, on the accuracy of predictive maps produced by bioclimatic models. Using data on the distribution of 129 species of woody plants in Israel, we tested the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
389
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(423 citation statements)
references
References 66 publications
14
389
0
4
Order By: Relevance
“…These results coincide with those of Kadmon et al (2004), who affirmed that bias in distributional data is common in the form of high concentrations of collection sites along roads. Souza-Baena et al (2013) also found road bias effects on plant data completeness across Brazil, and Hijmans et al (2000) reported that most gene bank accessions for wild potatoes in Bolivia were collected within 2 km of roads, 3-fold greater than random expectations.…”
Section: Completeness At Different Spatial Levelssupporting
confidence: 89%
“…These results coincide with those of Kadmon et al (2004), who affirmed that bias in distributional data is common in the form of high concentrations of collection sites along roads. Souza-Baena et al (2013) also found road bias effects on plant data completeness across Brazil, and Hijmans et al (2000) reported that most gene bank accessions for wild potatoes in Bolivia were collected within 2 km of roads, 3-fold greater than random expectations.…”
Section: Completeness At Different Spatial Levelssupporting
confidence: 89%
“…Although Kadmon et al (2004) found significant differences between the distribution of collection localities and that of the rainfall conditions based on a random selection of localities in the study area, they demonstrated that predictions of habitat suitability were not biased, since the statistical difference was weak (although significant). In this study, strong statistical differences were found and therefore we conclude that model predictions based on the current database are likely to produce biased and misleading estimates of species range predictions.…”
Section: Bias: a Recurrent Issuementioning
confidence: 75%
“…We used a similar approach to identify factors influencing spatial bias in the database and estimating environmental bias as implemented earlier by Kadmon et al (2004) and Loiselle et al (2008). Although Kadmon et al (2004) found significant differences between the distribution of collection localities and that of the rainfall conditions based on a random selection of localities in the study area, they demonstrated that predictions of habitat suitability were not biased, since the statistical difference was weak (although significant).…”
Section: Bias: a Recurrent Issuementioning
confidence: 99%
See 1 more Smart Citation
“…There are few records of where species were looked for but not found, i.e., sites with recorded and reliable absences (but see standardized ecological studies). Numerous examples exist where the maps of diversity generated with census information do not show the real distribution of species but, instead, they represent the maps of collections that were conducted according to their cultural or landscape interest, or for accessibility reasons (Kadmon et al 2004;Pautasso and McKinney 2007;Sánchez-Fernández et al 2008).…”
Section: Introductionmentioning
confidence: 99%